Application of Local Wisdom to Promote Added Value of Coconut Products Based on Creative Economy of Community Enterprises in Samut Songkram: การประยุกต์ภูมิปัญญาท้องถิ่นเพื่อสร้างมูลค่าเพิ่มในผลิตภัณฑ์มะพร้าว ตามแนวเศรษฐกิจสร้างสรรค์ของวิสาหกิจชุมชนจังหวัดสมุทรสงคราม - Laophuangsak, Phunthida (Journal of Applied Economics and Management Strategy, 2020)
บทคัดย่อ บทความวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาแนวทางการประยุกต์ภูมิปัญญาท้องถิ่นเพื่อสร้างมูลค่าเพิ่มในผลิตภัณฑ์มะพร้าวตามแนวเศรษฐกิจสร้างสรรค์ของวิสาหกิจชุมชนจังหวัดสมุทรสงคราม ใช้วิธีวิจัยเชิงคุณภาพ จากผู้ให้ข้อมูลหลักในการสัมภาษณ์ระดับลึก และการสนทนากลุ่ม รวม 17 คน ใช้เทคนิคการตรวจสอบแบบสามเส้า และการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า แนวทางการประยุกต์ภูมิปัญญาท้องถิ่นเพื่อสร้างมูลค่าเพิ่มในผลิตภัณฑ์มะพร้าว ตามแนวเศรษฐกิจสร้างสรรค์ของวิสาหกิจชุมชนจังหวัดสมุทรสงคราม จำแนกตามขั้นตอนของกระบวนการผลิต ได้แก่ 1) ระยะการสร้างผลิตผลด้วยการใช้ปัจจัยการผลิตที่มีคุณภาพดี และ เป็นทรัพยากรที่มีอยู่หรือแสวงหาได้ภายในท้องถิ่น เพื่อให้กระบวนการผลิตสินค้ามีประสิทธิภาพและมีคุณภาพ 2) ระยะการสร้างคุณค่าและมูลค่าเพิ่มให้กับผลิตผลด้วยการเพิ่มมูลค่าเชิงปริมาณ มูลค่าเชิงคุณภาพ และการเพิ่มโอกาส/ทางเลือกตามแนวทางเศรษฐกิจสร้างสรรค์ 3) ระยะการตลาดในเชิงพาณิชย์ด้วยการทำให้ผลิตผลน่าสนใจตรงกับความต้องการของตลาด และมีภาพลักษณ์ที่ดีในมุมมองของผู้บริโภค ภายใต้เงื่อนไขการเปลี่ยนแปลงของธรรมชาติและสิ่งแวดล้อม วิถีชีวิต และการพัฒนาหรือต่อยอดจากภูมิปัญญาเดิม ก่อให้เกิดการลดรายจ่าย การเพิ่มรายได้ และการสร้างโอกาสหรือเกิดทางเลือกที่หลากหลาย Abstract The objective of this research was to study guidelines for the application of local wisdom to promote the added value of coconut products based on the creative economy of community enterprises in Samut Songkram in Thailand. Quality research methodology was employed using 17 key informants for in-depth interviews and focus-group discussion. Data analysis was carried out using the triangulation technique and content analysis. The results of the study revealed that the guidelines for the application of local wisdom to promote the added value of coconut products based on a creative economy were classified based on the stages of the production processes. The first stage was the primary stage of production using good-quality production factors for good agricultural practices, and effective productivity with the best produce; further, agricultural resources should be easily found locally. Second, a stage for promoting added value by adding quantitative and qualitative values, as well as the availability of opportunities and choices based on a creative economy, should be created. Third, a stage for commercial marketing by launching products that meet marketing needs and have a positive image according to the consumers’ perspectives should also be created. These processes should rely on the application of local wisdom to promote added value under the following circumstances: changes in nature and in the environment, ways of life and work, and the development or improvement of indigenous knowledge, which causes reduced expenditure, increases in income, and multiple opportunities and diversified alternatives.